DEVELOPING A BANGKA BELITUNG CULTURAL - BASED ENGLISH TEXTBOOK FOR TOURISM VOCATIONAL STUDENTS - Handayani, Rindu; Aprilliandari, Dwi Indra (Premise: Journal of English Education and Applied Linguistics, 2022)
This research aims to develop and provide vocational school students with a cultural-based English textbook to understand English better. Based on a mini-interview with some English teachers and observation conducted in some senior high schools in Bangka Belitung, cultural aspect has never been introduced to the classrooms due to their limited teaching timing, diverse textbooks' syllabus, and various learning objectives done. The method used in this study is Research and Development (R&D) by Dick, Carey, and Carey model. The data analysis was conducted quantitatively by the Likert scale. The product is said feasible based on the expert assessments, teachers' evaluations, and students' post-test results. The score obtained from the content expert was 82%, the media expert shares 84.05%, the teachers' evaluations' score was 83.14%, and the students' post-tests reached 78.15, which was higher than the pre-test (67.95). It is summarized that developing a cultural-based English textbook is necessary and immediately necessary. Further researchers are expected to carry out a larger subject scale and include all English aspects in the book's production